Efficient numerical modelling of wave-structure interaction - Siddorn, P; Philip Siddorn (2012)
Offshore structures are required to survive in extreme wave environments. Historically, the design of these offshore structures and vessels has relied on wave-tank experiments and linear theory. Today, with advances in computing power, it is becoming feasible to supplement these methods of analysis with fully nonlinear numerical simulation. This thesis is concerned with the development of an efficient method to perform this numerical modelling, in the context of potential flow theory. The interaction of a steep ocean wave with a floating body involves a moving free surface and a wide range of length scales. Attempts to reduce the size of the simulation domain cause problems with wave reflection from the domain edge and with the accurate creation of incident waves. A method of controlling the wave field around a structure is presented. The ability to effectively damp an outgoing wave in a very short distance is demonstrated. Steep incident waves are generated without the requirement for the wave to evolve over a large time or distance before interaction with the body. This enables a general wave-structure interaction problem to be modelled in a small tank, and behave as if it were surrounded by a large expanse of water. The suitability of the boundary element method for performing this modelling is analysed. Potential improvements are presented with respect to accuracy, robustness, and computational complexity. Evidence of third order diffraction is found for an FPSO model.